2020
DOI: 10.3145/epi.2020.jul.02
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 communication management in Spain: Exploring the effect of information-seeking behavior and message reception in public’s evaluation

Abstract: How to cite this article: Moreno, Ángeles; Fuentes-Lara, Cristina; Navarro, Cristina (2020). "Covid-19 communication management in Spain: Exploring the effect of information-seeking behavior and message reception in public's evaluation". El profesional de la información, v. 29, n. 4, e290402.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 48 publications
2
72
0
20
Order By: Relevance
“…Social media play an important role in providing information about COVID-19 (Cinelli et al, 2020;Mohd Hanafiah, & Wan, 2020;Moreno et al, 2020;Thelwall & Thelwall, 2020). For example, in Spain, Moreno et al (2020) found evidence that messenger services are the second most important source of information.…”
Section: Exposure To Misinformation In Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Social media play an important role in providing information about COVID-19 (Cinelli et al, 2020;Mohd Hanafiah, & Wan, 2020;Moreno et al, 2020;Thelwall & Thelwall, 2020). For example, in Spain, Moreno et al (2020) found evidence that messenger services are the second most important source of information.…”
Section: Exposure To Misinformation In Social Mediamentioning
confidence: 99%
“…Social media play an important role in providing information about COVID-19 (Cinelli et al, 2020;Mohd Hanafiah, & Wan, 2020;Moreno et al, 2020;Thelwall & Thelwall, 2020). For example, in Spain, Moreno et al (2020) found evidence that messenger services are the second most important source of information. Given their enormous scope, a cause for concern is derived from the empirical finding that misinformation spreads easily through social media ENDORSEMENT OF CLAIMS ABOUT COVID-19 12 platforms (Vosoughi et al, 2018).…”
Section: Exposure To Misinformation In Social Mediamentioning
confidence: 99%
“…Mesmo quando as informações de perfis oficiais do governo são verídicas, a quantidade excessiva de informações recebidas faz com que alguns cidadãos se sintam incapazes em diferenciar quais mensagens apresentam informações inconsistentes ou não (Moreno, Fuentes-Lara, Navarro 2020). Como forma de reduzir a quantidade de notícias falsas na plataforma, o Facebook tem tomado algumas medidas de controle.…”
Section: Discussionunclassified
“…La investigación emergente destaca la importancia de las redes sociales porque brindan de manera rápida una información actualizada y sin filtros (Procopio & Procopio, 2007;Tai & Sun, 2007) y apoyo emocional durante crisis (Macias, Hilyard & Freimuth, 2009;Jin, Liu & Austin, 2014). El uso de las redes sociales aumenta durante eventos de crisis (Fraustino, Liu & Jin, 2017), y esta tendencia sigue creciendo exponencialmente (Thompson, Mazer, Payne, Jerome, Kirby & Pfohl, 2017;Reuter & Kaufhold, 2018;Moreno, Fuentes-Lara & Navarro, 2020). No obstante, constituyen además, un medio veloz para la propagación de rumores, noticias falsas y por tanto desinformación (González, 2019;Moscadelli et al, 2020;Orso, Federici, Copetti, Vetrugno & Bove, 2020;Allahverdipour, 2020;Andreu-Sánchez & Martín-Pascual, 2020), temas y elementos que todavía necesitan ser investigados y que son objeto de estudio de la infodemiología.…”
Section: La Comunicación Del Riesgo De Salud Durante Epidemias Y Pandunclassified